2012
DOI: 10.1039/c2cp40244k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast vibrational dynamics of SCN− and N3− in polar solvents studied by nonlinear infrared spectroscopy

Abstract: In this paper, we report on our investigation into the vibrational dynamics of the antisymmetric stretching modes of SCN(-) and N(3)(-) in several polar solvents. We used an infrared (IR) pump-probe method to study orientational relaxation processes. In two aprotic solvents (N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO)), the anisotropy decay shows a bimodal feature, whereas in other solvents the anisotropy decay can be fitted well by a single exponential function. We consider that the relative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 65 publications
4
43
0
Order By: Relevance
“…Several groups including us experimentally and theoretically examined the frequency fluctuations of ions in water and pure water and revealed that the characteristic time constant of approximately 1 ps reflects fluctuations of hydrogen-bonding network in liquid water. [9][10][11][12][13][55][56][57][58] Consistent with the results of the threepulse IR photon echo experiment for N 3 − in D 2 O, 12,13 we also found that FFTCFs decay with a time constant of 1.3 ps for N 3 − in H 2 O. Moreover, we showed that FFTCF of N 3 -Ala and N 3 -Pro are also characterized by time constants of about 1.5 ps and 1.0 ps, respectively.…”
Section: Spectral Diffusionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several groups including us experimentally and theoretically examined the frequency fluctuations of ions in water and pure water and revealed that the characteristic time constant of approximately 1 ps reflects fluctuations of hydrogen-bonding network in liquid water. [9][10][11][12][13][55][56][57][58] Consistent with the results of the threepulse IR photon echo experiment for N 3 − in D 2 O, 12,13 we also found that FFTCFs decay with a time constant of 1.3 ps for N 3 − in H 2 O. Moreover, we showed that FFTCF of N 3 -Ala and N 3 -Pro are also characterized by time constants of about 1.5 ps and 1.0 ps, respectively.…”
Section: Spectral Diffusionsupporting
confidence: 89%
“…9 We have reported the temperature dependence of vibrational dynamics of N 3 − in water and the vibrational dynamics of OCN − and SCN − in methanol. [10][11][12][13] Recently, artificial amino acids which are labeled by azide or thiocyanate groups have been shown to be excellent vibrational probes to study the dynamics in water and biological environments. Bloem et al incorporated an azide probe into peptide and studied the spectral diffusion process of the N 3 anti-symmetric stretching mode in protein.…”
Section: Introductionmentioning
confidence: 99%
“…Hydration of ions in aqueous media has been a major area of scientific studies [1][2][3][4] in chemical, biological, and many other branches of science. The structure and dynamics of water around ions have been investigated extensively by means of experimental, [5][6][7][8][9][10][11] theoretical, [12][13][14][15][16][17][18][19][20] and also combination of both the methods. [21][22][23][24][25] The polyoxy-anions form a major class of ions which have great relevance to various atmospheric and biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, such ion-molecule interactions have been extensively studied by FTIR experiments and theoretical methods for a few decades [1][2][3][4][5][6][7]. However, the effect of ions on vibrational dynamics of a given molecule has begun to be investigated recently with an advent of time-resolved vibrational spectroscopic techniques such as ultrafast infrared-Raman, infrared pump-probe (IR PP), and two-dimensional IR (2DIR) experiments [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A vibrationally excited molecule undergoes different relaxation processes on various timescales including vibrational energy transfer to anharmonically coupled vibrational modes [23,24], vibrational energy dissipation into the solvent [25], and resonance energy transfer to nearby vibrational modes with similar vibrational energies [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%